2011
DOI: 10.1186/1472-6874-11-51
|View full text |Cite
|
Sign up to set email alerts
|

Baropodometry on women suffering from chronic pelvic pain - a cross-sectional study

Abstract: BackgroundPrevious studies have associated chronic pelvic pain with a stereotyped pattern of movement and posture, lack of normal body sensations, a characteristic pain distribution. We aimed at evaluating if these postural changes are detectable in baropodometry results in patients with chronic pelvic pain.MethodsWe performed a prospective study in a university hospital. We selected 32 patients suffering from chronic pelvic pain (study group) and 30 women without this pathology (regular gynecological work out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…Mean plantar pressure is generally used to detect imbalances in the anteroposterior and mediolateral directions (Keijsers et al, 2009). Therefore, this method is very important to understand the adaption of a modified orthostatic position which could result in/from an erratic postural adaptation, secondary to certain diseases that affect, or can be affected by posture (Kaercher et al, 2011;Bricot, 2008).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mean plantar pressure is generally used to detect imbalances in the anteroposterior and mediolateral directions (Keijsers et al, 2009). Therefore, this method is very important to understand the adaption of a modified orthostatic position which could result in/from an erratic postural adaptation, secondary to certain diseases that affect, or can be affected by posture (Kaercher et al, 2011;Bricot, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…The principle is to map the pressure of the plantar surface, which, indirectly, indicates important postural abnormalities (Bellizzi et al, 2011;Kaercher et al, 2011). Computerized baropodometry furnishes useful information on the positioning of the foot.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring of plantar pressure is becoming very popular in clinical, sports, and design of footwear and rehabilitation studies. This technology can help to identify and analyze pathologies, muscular defects, postural anomalies, design of footwear, geometry of outsole and evaluate gait and standing posture [1][2][3][4]. There are some technologies that have developed to measure foot plantar pressures but most of those devices are high cost and not available to the researchers from lower developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have demonstrated that women with endometriosis have generalized hyperalgesia in body areas beyond the site of ectopic implants, mediated by sensitization of central pain circuits (4, 5). This is consistent with animal studies demonstrating that induced endometriosis results in vaginal hyperalgesia (6).…”
Section: Introductionmentioning
confidence: 99%